2008
DOI: 10.1097/fpc.0b013e3282f56176
|View full text |Cite
|
Sign up to set email alerts
|

Association between glutathione S-transferase A1, M1 and T1 polymorphisms and hypertension

Abstract: The importance of oxidative stress in hypertension has recently received increasing attention. The association between the incidence of hypertension and a super family of antioxidant enzymes, glutathione S-transferase (GST)A1, GSTM1 and GSTT1, polymorphisms was investigated in 468 Japanese participants in a health screening program. The frequency of the GSTA1*B allele carriers was significantly higher in hypertensive patients than normotensive participants [adjusted odds ratio (OR): 1.8; 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Also, the combined effect of the GSTP1 and GSTM1 variant genotypes on the risk of AD tended to be higher than the effect of GSTP1 or GSTM1 variants alone. Similar to our findings, several studies have indicated that the influences of GST genotypes on disease risk become more significant with an increase in the number of GST variant alleles (29)(30)(31). This is likely due to GST enzymes having similar substrate specificities.…”
Section: Discussionsupporting
confidence: 79%
“…Also, the combined effect of the GSTP1 and GSTM1 variant genotypes on the risk of AD tended to be higher than the effect of GSTP1 or GSTM1 variants alone. Similar to our findings, several studies have indicated that the influences of GST genotypes on disease risk become more significant with an increase in the number of GST variant alleles (29)(30)(31). This is likely due to GST enzymes having similar substrate specificities.…”
Section: Discussionsupporting
confidence: 79%
“…Because GST M1 and T1 null genotypes result in a complete absence of activity in their respective enzymes [52,68], these common deletion polymorphisms have been widely investigated for their effect on the risk of myocardial infarction [142], hypertension [80,103], and smoking-related and nonrelated coronary artery disease (CAD); [1,50,54,84,130,140]. However, these studies have yielded contradictory results, with some studies showing a significant association, and others showing no such association [140].…”
Section: Discussionmentioning
confidence: 99%
“…However, those that exist indicate that the GSTA1*-69C/T polymorphism is a potential genetic marker for cardiovascular death risk in end-stage renal disease patients [33], and a genetic risk factors for essential hypertension [34]. In the study of Oniki and collaborators, GSTA1*-69C was positively associated with the arterial hypertension in a Japanese sample.…”
Section: Page 8 Of 14mentioning
confidence: 96%